Discovery of an outflow of the very low-mass star ISO 143 - Joergens, Viki; Kopytova, Taisiya G.; Pohl, Adriana (Astronomy and astrophysics, 2012)
We discover that the very young very low-mass star ISO 143 (M5) is driving an outflow based on spectro-astrometry of forbidden [S II] emission lines at 6716 Å and 6731 Å observed in UVES/VLT spectra. This adds another object to the handful of brown dwarfs and very low-mass stars (M5-M8) for which an outflow has been confirmed and which show that the T Tauri phase continues at very low masses. We find the outflow of ISO 143 to be intrinsically asymmetric and the accretion disk to not obscure the outflow, as only the red outflow component is visible in the [S II] lines. ISO 143 is only the third T Tauri object showing a stronger red outflow component in spectro-astrometry, after RW Aur (G5) and ISO 217 (M6.25). We show here that, including ISO 143, two out of seven outflows confirmed in the very low-mass regime (M5-M8) are intrinsically asymmetric. We measure a spatial extension of the outflow in [S II] of up to 200-300 mas (about 30-50 AU) and velocities of up to 50-70 km s-1. We furthermore detect line emission of ISO 143 in Ca II (8498 Å), O I (8446 Å), He I (7065 Å), and weakly in [Fe II] (7155 Å). Based on a line profile analysis and decomposition we demonstrate that (i) the Ca II emission can be attributed to chromospheric activity, a variable wind, and the magnetospheric infall zone, (ii) the O I emission mainly to accretion-related processes but also a wind, and (iii) the He I emission to chromospheric or coronal activity. We estimate a mass outflow rate of ISO 143 of ~10-10 M⊙ yr-1 and a mass accretion rate in the range of ~10-8 to ~10-9 M⊙ yr-1. These values are consistent with those of other brown dwarfs and very low-mass stars. The derived Ṁout/Ṁacc ratio of 1-20% does not support previous findings of this number being very large (>40%) for very low-mass objects.